Study on the resilience of historical blocks under the process of high-speed urbanization: Take the renewal of Longjin River in Shajing Ancient Fair in Shenzhen as an example - Zhou, Ziwei; Ding, Lingzhen; Fu, Yuqi (International Planning History Society Proceedings, 2024)
As the largest existing mixed historical block in Shenzhen, Shajing Ancient Fair is a mixture of historical and modern living styles. By studying the theory of urban resilience and taking the transformation of the Longjin River in Shajing Ancient Fair as the starting point, this paper analyzes the vulnerability and resilience characteristics of historical block in the process of high-speed urbanization and provides ideas for the protection and development of cultural heritage in the process of urbanization. In the process of Shenzhen's urbanization, Shajing Ancient Fair is faced with problems such as mass migration of population, changes in land power, transformation in the economic modes, deterioration of living conditions, etc., which reflects the vulnerability of historical blocks. To avoid the resilience fatigue of ancient fairs and repair the vulnerability of historical blocks, river channel transformation is used as an opportunity to improve spatial resilience, ecological resilience, economic resilience, and institutional resilience of mixed historical block in the process of urbanization. This paper focuses on the measures to improve spatial and ecological resilience in the transformation of Shajing Ancient Fairs. Specific approaches include: 1) To improve spatial resilience, use the "acupuncture" renewal method to revitalize the main public space along the river; 2) to improve ecological resilience, divert rain and pollution and rebuild non-motor vehicle parking lots. By summarizing the impact of Longjin River micro-renewal, this study provides a systematic mechanism from the perspective of urban resilience for the beautification of the environment, industrial value-added, and infrastructure optimization of historical blocks.